Features of subset composition and functional activity of blood lymphocytes in tick-borne infections of different etiologies - O. V. Voronkova; E. N. Ilyinskikh; R. R. Hasanova; I. E. Esimova; K. V. Nevskaya; M. R. Karpova; N. A. Chernyshov; A. V. Yampolskaya; O. V. Yampolskaya (Бюллетень сибирской медицины)
Aim. To perform a comparative assessment of subset composition and functional activity of peripheral blood lymphocytes in patients with tick-borne encephalitis (TBE) and ixodid tick-borne borreliosis (ITBB) in the acute phase of the disease.Materials and methods. The study involved 22 patients with febrile and meningeal TBE, 15 patients with ITBB with and without erythema, and 11 healthy controls. Subset composition of blood lymphocytes was determined by flow cytometry. The blast transformation assay was applied to assess lymphocyte proliferation. Cytokine-producing activity of cells was studied in 24-hour incubated mononuclear cell cultures. Cytokine concentrations (interleukin (IL)-2, IL-4, IL-10, interferon (IFN)γ) were determined in the supernatants by the enzyme-linked immunosorbent assay (ELISA).Results. Patients with TBE demonstrated an increase in the proportion of helper – inducer T-cells, a pronounced decrease in the proportion and absolute count of cytotoxic T cells, and low T lymphocyte count compared to the control values. The study in ITBB patients revealed an increase in the helper – inducer T-cell count and the proportion of NK-cells, a decrease in the cytotoxic T cell count, and the T lymphocyte count comparable to normal values. The most significant decrease in the levels of phytohemagglutinin-induced lymphocyte proliferation was found in patients with TBE. Patients of both groups showed a decrease in IL-2 secretion in the mononuclear cell culture, a rise in IL-4 and IL-10 production, and IFNγ production levels comparable to control values.Conclusion. The study of TBE patients revealed relative lymphocytopenia with changes in the subset composition of lymphocytes characterized by an increase in the proportion of helper – inducer T-cells and a decrease in the absolute cytotoxic T lymphocyte count. Patients with ITBB demonstrated an increase in the proportion of NK-cells and a more pronounced imbalance in the T-helper / cytotoxic T lymphocyte ratio. Changes in the functional phenotype of lymphocytes, regardless of the etiology of tick-borne infection, were characterized by reduced proliferative reserve, low IL-2 secretion, increased IL-4 and IL-10 production, and depressed reactivity of lymphocytes with respect to IFNγ secretion.